(untitled) (Bangladesh Veterinarian, 2016)
Peste des petits ruminants (PPR) is a highly contagious acute viral disease of domestic and wild ruminants particularly goats and sheep, which causes severe economic losses. Since 1993 PPR has been endemic in goats in Bangladesh. The present study was a seroprevalence study of PPR antibodies in goats and cattle at St. Martin’s Island in Bangladesh from July 2012 to June 2013. There was no previous history of Rinderpest or PPR outbreak, and no Rinderpest vaccination. Blood samples were collected from 192 goats and 132 cattle randomly. All animals were apparently healthy, and were not vaccinated against Rinderpest or PPR. Serum antibody titre (competition percentage; CP value) was determined by a commercially available c-ELISA kit. The overall seroprevalence of PPR in goats was 37.5%. No serum samples from cattle were positive. In view of the high risk of PPR, a control strategy is proposed. Bangl. vet. 2014. Vol. 31, No. 2, 55-59